2011
DOI: 10.1007/s12603-011-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, cognitive impairment and mortality among the oldest old

Abstract: Among the oldest old, frailty status was significantly associated with cognitive impairment; after adjustment, frailty alone was predictive of subsequent mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
85
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 29 publications
8
85
1
11
Order By: Relevance
“…The risk of frail individuals exhibiting a decline in cognitive function in a 12-month period, as evaluated by the MMSE, was approximately fivefold greater in comparison to non-frail individuals. Previous studies with a longer follow-up period also report an association between frailty and cognitive decline measured by the MMSE 4,6,8 .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The risk of frail individuals exhibiting a decline in cognitive function in a 12-month period, as evaluated by the MMSE, was approximately fivefold greater in comparison to non-frail individuals. Previous studies with a longer follow-up period also report an association between frailty and cognitive decline measured by the MMSE 4,6,8 .…”
Section: Discussionmentioning
confidence: 79%
“…The association between frailty and cognitive impairment is widely discussed in the literature [3][4][5][6][7] . While studies have shown that frailty may be a predictor of mild cognitive impairment, dementia and cognitive decline, there seems to be a biological association between the onset of cognitive decline and frailty [3][4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that psychological and social problems can accelerate the development of disability, hospitalization, nursing home placement and death (14)(15)(16)(17)(18)(19)(20). In some cases the reasons for the synergistic effect are obvious while in others they are more complex and may depend on similar pathophysiological processes accelerating both problems (1,21).…”
mentioning
confidence: 99%